Relational thinking styles and natural intelligence assessing inference patterns for computational modeling - Chiasson, Phyllis; Tristan, Jayne, 1952-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"The science of intelligence has created a plethora of theories and measurements, which have various applications of both computational, social, and managerial significance. Relational Thinking Styles and Natural Intelligence: Assessing Inference Patterns for Computational Modeling explores a specific set of intelligence theories, unifying and quantifying to create a verifiable model of various inferencing habits. Relational Thinking Styles suggests that the inferencing patterns described and demonstrated by this model may provide a platform from which to examine and integrate various aspects of natural intelligence and how these are expressed. This research provides valuable information for businesses, social services, and any decision-making process involving intelligence assessment"--Provided by publisher.
1. Definitions of terms -- 2. Why understanding thinking styles matters -- 3. Structure of the relational thinking styles model -- 4. Assessing inference patterns -- 5. Algorithms for determining thinking styles -- 6. Some variables for computationally modeling RTS -- 7. Computationally modeling inference patterns -- 8. Implications and applications of relational thinking styles -- 9. Phenomenology : the qualitative core of reasoning -- 10. Peirce's normative sciences -- 11. The dilemma of defining abduction -- 12. Creative abduction.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed March 20, 2012).
Keywords: Thought and thinking; Inference; Methodology; Basic inferencing algorithms; Creativity; Computational modeling; Human systems theory; Inference patterns; Intelligence modeling applications; Normative science; Reasoning classification; Relational thinking styles; Semiotic structure; Electronic books